Mobile phone based pregnancy support system - Maniam, Jayanthy *; Chin, Chee Ken *; Chenapiah, Kanaga * (2007)
Being pregnant can be very challenging to mothers especially if they are expecting for the first time. Many rely on information that is past down from one to another which may not be accurate as experience from each pregnancy can be different from one pregnancy to the other and from one person to another. Matters are made worse when information past down is mixed with cultural taboo. This paper presents the framework and prototype of mobile phone based pregnancy system based on preliminary study conducted among the pregnant mothers and their spouses in a local private hospital and few maternity clinics. This study provided the basis for the personalised and localised content development for mobile phone on the health care for pregnant mothers, due date calculation, calendar, growth of fetus, complications, medication, drug and health alerts. Mobile phone based pregnancy support can position itself as a major breakthrough approach to educate women on pregnancy, monitor their own and child?s progress, follow up with medical checkups, critical updates and post delivery support through mobile phone. This will reduce the anxiety and stress among pregnant mothers. Women in rural area can benefit through this system greatly by preparing for child birth and post delivery.